Desain Sistem Pendingin Kemasan Baterai Litium Ion Kapasitas Pengisian Cepat dengan PCM (Phase Change Material) dan Pelat Pendingin - Choirul Anwar; Agus Suprayitno (JURNAL KAJIAN TEKNIK MESIN, 2021)
Battery performance is affected by the problem of overheating which can cause mechanical damage to the battery and electronic components of the BMS (Battery Management System). With the need for an increase in battery charging time with fast capacity, the internal heat generated by the battery also increases so that the battery pack needs to be equipped with a cooling system. Currently, the cooling system in the battery pack uses a lot of cooling plate, cooling pipe, PCM (Phase Change Material) and cooling fluid. Combining cooling system design based on advantages and disadvantages to produce the best performance was tried using the cooling plate and PCM. The method used is to change the initial design of the battery pack without cooling to a cooling system by making a design and verifying the design. The process of thermal analysis is carried out in the process of charging the battery and removing the battery. The result of the research is the distribution of heat transfer that occurs during the battery charging process and the battery discharge is uniform and the temperature value obtained is the 43,2 °C battery discharge process in the main cooling plate component and the maximum temperature in the charging process is 57,6°C. at BMS. Cooling using a cooling plate and PCM for a closed system is maximized. Keywords: baterai Litium-Ion, Heat Sink, PCM